Konkurencyjność przedsiębiorstw agrobiznesu (studium przypadku przedsiębiorstwa "PASZMARK") - Chrobocińska, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The main aim of this article was to identify and determine intensity of factors influencing competitiveness of the enterprise "Paszmark". The results of the research have proved that the most important factor was competition. The enterprise uses in competitiveness' fight Customers Relationship Management techniques and additionally offers high quality product. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 128-135